AGA452: Introduction to Horticulture / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (Universiti Teknologi MARA (UiTM), 2020)
This course is designed to introduce students to overview area and concepts involved in horticulture. Students will be introduced branches in horticulture, plant classification in horticulture, plant growth, metabolism and requirement, propagation technique and practices through theoretical and field work. This course will strengthen the students with a strong interest in horticulture by exposing them on technology and the current trends involve in the horticulture industry.